2013
DOI: 10.1097/inf.0b013e318270d850
|View full text |Cite
|
Sign up to set email alerts
|

Density Interactions Among Streptococcus pneumoniae, Haemophilus influenzae and Staphylococcus aureus in the Nasopharynx of Young Peruvian Children

Abstract: Streptococcus pneumoniae, Haemophilus influenzae and Staphylococcus aureus are commonly carried in the nasopharynx (NP) of young children, and have been speculated to interact with each other. Although earlier studies used cultures alone to assess these interactions, the addition of real-time quantitative polymerase chain reaction (qPCR) provides further insight into these interactions. We compared results of culture and qPCR for the detection of these three bacteria in 446 NP samples collected from 360 health… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
83
1
4

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 86 publications
(96 citation statements)
references
References 40 publications
8
83
1
4
Order By: Relevance
“…Old mice are unable to clear bacterial colonization as effectively as their young counterparts. We observed a number of interspecies interactions between S. pneumoniae and the existing mouse microbiome (e.g., Staphylococcus) that have been reported previously only in experimental models (16)(17)(18)(19)(20)(21)(22)(23)(24). In particular, Streptococcus interacted competitively with Staphylococcus and synergistically with Haemophilus.…”
mentioning
confidence: 58%
See 3 more Smart Citations
“…Old mice are unable to clear bacterial colonization as effectively as their young counterparts. We observed a number of interspecies interactions between S. pneumoniae and the existing mouse microbiome (e.g., Staphylococcus) that have been reported previously only in experimental models (16)(17)(18)(19)(20)(21)(22)(23)(24). In particular, Streptococcus interacted competitively with Staphylococcus and synergistically with Haemophilus.…”
mentioning
confidence: 58%
“…Contrary to S. pneumoniae's interaction with Staphylococcus, Haemophilus facilitates S. pneumoniae's survival, as shown in previous studies using nasopharyngeal samples of children between 0 and 35 months of age (23). Although the exact mechanisms are unclear, it has been suggested that this phenomenon is related to the downregulation of pneumococcal autolysis and fratricide genes, as well as an increase in pneumococcal biofilm formation (19,23,24). As a result, there is decreased production of pneumococcal cell wall hydrolase and a subsequent decrease in pneumococcal lysis during the presence of Haemophilus influenzae.…”
Section: Discussionmentioning
confidence: 85%
See 2 more Smart Citations
“…Accelerating pneumococcal clearance is therefore also a goal of new vaccines (51); however, success of such prevention strategies in the elderly will require intact innate signaling, including epithelial responses, lymphoid tissue function, and phagocyte function. So far, there is no clear evidence of a longer duration of human carriage in the elderly compared to young adults, although this might be a consequence of scarce longitudinal colonization data for adults and the elderly or of the relatively low sensitivity of conventional detection methods (52)(53)(54).…”
Section: Figmentioning
confidence: 99%